2015
DOI: 10.1021/acs.molpharmaceut.5b00168
|View full text |Cite
|
Sign up to set email alerts
|

Factors Governing P-Glycoprotein-Mediated Drug–Drug Interactions at the Blood–Brain Barrier Measured with Positron Emission Tomography

Abstract: The adenosine triphosphate-binding cassette transporter P-glycoprotein (ABCB1/Abcb1a) restricts at the blood–brain barrier (BBB) brain distribution of many drugs. ABCB1 may be involved in drug–drug interactions (DDIs) at the BBB, which may lead to changes in brain distribution and central nervous system side effects of drugs. Positron emission tomography (PET) with the ABCB1 substrates (R)-[11C]verapamil and [11C]-N-desmethyl-loperamide and the ABCB1 inhibitor tariquidar has allowed direct comparison of ABCB1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 54 publications
4
67
0
Order By: Relevance
“…In Human, [ 11 C]dLop was shown to be poorly metabolized, allowing for accurate estimation of the P-gp function at the BBB. [ 11 C]dLop brain distribution was shown to be sensitive to P-gp inhibition in both the human and non-human primates using prototypical P-gp inhibitors such as DCPQ (Liow et al, 2009) or tariquidar (Kreisl et al, 2010), although being less sensitive than [ 11 C]verapamil to detect partial and low degree of P-gp inhibition using tariquidar in mice (Wanek et al, 2015). Non-human primates have been shown to be more relevant than rodents to study P-gp function at the BBB, given the high differences in P-gp expression between rodents and primates (Hoshi et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…In Human, [ 11 C]dLop was shown to be poorly metabolized, allowing for accurate estimation of the P-gp function at the BBB. [ 11 C]dLop brain distribution was shown to be sensitive to P-gp inhibition in both the human and non-human primates using prototypical P-gp inhibitors such as DCPQ (Liow et al, 2009) or tariquidar (Kreisl et al, 2010), although being less sensitive than [ 11 C]verapamil to detect partial and low degree of P-gp inhibition using tariquidar in mice (Wanek et al, 2015). Non-human primates have been shown to be more relevant than rodents to study P-gp function at the BBB, given the high differences in P-gp expression between rodents and primates (Hoshi et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In human, Kreisl et al reported a 5-fold increase in AUC 10-30 using tariquidar 4 mg/kg as an inhibitor and hypothesized that P-gp remained only partially inhibited in this condition (Kreisl et al, 2015). In rats, P-gp inhibition using high dose CsA (50 mg/kg) resulted in a smaller 3.5-fold increase in the brain-to-plasma concentration ratio, estimated using the total volume of distribution (V T ) in the 1-tissue compartment model (Farwell et al, 2013), although the in vitro transport of [ 11 C]dLop was shown similar in P-gp overexpressing cells transfected using either the rodent Abcb1a or the human ABCB1 gene (Wanek et al, 2015). The brain-to-plasma ratio observed in anesthetized mice was only 6 to 7-fold higher in P-gp deficient (Abcb1a/1b (-/-) ) as compared with wild-type mice (Lazarova et al, 2008;Wanek et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, cells that constitute the BBB express enhanced levels of active drug efflux transporters of the ATP-binding cassette (ABC) gene family, which have been recognized as key determinants of drug distribution to, and elimination from, the CNS (58,77). The most widely characterized transporter of the ABC family is P-glycoprotein (P-gp), which has been a subject of numerous investigations and for years was considered a major obstacle in the delivery of therapeutics into the brain (78,79). Recent studies indicated P-gp function is largely supported by the breast cancer resistance protein (BCRP), and overexpression of BCRP is associated with resistance to a wide range of different anticancer agents including mitoxantrone, camptothecins, anthracyclines, flavopiridol and antifolates (80,81).…”
Section: Initiation and Maintenance Of Growth At Secondary Sitesmentioning
confidence: 99%